Who is afraid of the Friedman rule? - Joydeep Bhattacharya; Joseph Haslag; Antoine Martin; Rajesh Singh (Federal Reserve Bank of New York, 2005)
We explore the connection between optimal monetary policy and heterogeneity among agents. We utilize a standard monetary economy with two types of agents that differ in the marginal utility they derive from real money balances — a framework that produces a nondegenerate stationary distribution of money holdings. Without type-specific fiscal policy, we show that the zero-nominal-interest-rate policy (the Friedman rule) does not maximize type-specific welfare; further, it may not maximize aggregate ex ante social welfare. Indeed one or, more surprisingly, both types of agents may benefit if the central bank deviates from the Friedman rule.
Keywords: E31; E51; E58; 330; Geldpolitik; Regelgebundene Politik; Zinspolitik; Geldmengensteuerung; Theorie